Oral lichenoid reactions during antimalarial prophylaxis with sulphadoxine-pyrimethamine combination - Zain, R.B. (Southeast Asian Ministers of Education Organisation, 1989)
The prevalence of clinically observed oral lichenoid reaction in 186 Malay army personnel using Fansidar for 9 weeks was found to be 4.8. The prevalence was found to be 0.5 in 186 army personnel who had stopped using Fansidar for 2 months and 0 in 143 army personnel (control group) who had not used Fansidar for at least 4 months. The lesion showed a higher prevalence for the gingiva. There was no correlation between cigarette smoking and the occurrence of these lesions in each group